Penyuluhan Manfaat Produk Turunan Sawit Bagi Kesehatan Bagi Siswa Kelas X di SMAN 1 Kuok, Kampar - Fatmayati Fatmayati; Nina Veronika; Sri Wahyuni; Nur Asma Deli; Hanifah Khairiah; Antonius Jumadi Sihotang; Umar Linggom; Ivan Fadhillah (Politeknik Kampar, 2025)
This Community Service (PkM) activity aimed to enhance the knowledge of 10th-grade students at SMAN 1 Kuok, Kampar Regency, regarding the sustainable palm oil industry, palm oil processing, and the health benefits of its derivative products, especially red palm oil. The background of the activity was the students' lack of knowledge about palm oil and its derivatives, despite living in a palm oil plantation hub. The implementation methods included a location survey and needs analysis, knowledge and technology transfer, active partner participation, interactive counseling, and evaluation through pre-test and post-test. The results showed high enthusiasm from the participants. Questionnaire-based evaluation revealed that the activity was considered highly beneficial and successfully improved students' understanding of palm oil, its derivative products, and their health benefits. It was concluded that this PkM activity was effective in increasing students' knowledge and is expected to encourage their role as agents of change in supporting the sustainable palm oil industry in their region.